ILLOCUTIONARY ACTS IN WONDER WOMAN MOVIE (2017) - Waruwu, Elisabeth; Laiya, Rebecca Evelyn; Laia, Mohammad Yunus (Universitas Nias Raya, 2021)
In this research, the writer discuss the using of illocutionary acts in the utterance of each character in Wonder Woman Movie. The aims of the research are to find out the types of illocutionary act and also to find out the dominant types of illocutionary act which deal with this research. There are five types of illocutionary act: assertives, directives, commisives, expressives, and declaratives. The writer used qualitative descriptive analysis method. The writer collected the data from the script of Wonder Woman movie, then identifying and classifying of illocutionary act, and describing the context related to this research. The writer used content analysis in analysing data according to speech act theory of Searle. The result showed that four types illocutionary acts in this research. Those were: Assertives with total amount 31 utterancess contained paradigm cases of statements, descriptions, and explanations; directives with total amount 10 utterances contained paradigm cases of request and commands; commissives with total amount 3 utterances contained paradigm cases of promises and pledge: expressives with total amount 3 utterances contained paradigm cases apologies and thanks. In this research assertives become as the dominant types of illocutionary acts used in Wonder Woman movie. But in this research declaratives was not found based on used research theory. This study is expected to give some useful for reader insights in understanding what illocutionary acts is.